1979
DOI: 10.1073/pnas.76.12.6637
|View full text |Cite
|
Sign up to set email alerts
|

Human cell lines containing Epstein-Barr virus but distinct from the common B cell lymphoblastoid lines.

Abstract: In the majority of the lymphoblastoid cell lines obtained by transformation of human lymphocytes with Epstein-Barr virus (EBV), the cells are highly variable in shape and they grow in clumps in stationary cultures (1). They express many characteristics of normal B lymphocytes (2, 3). In particular, synthesis of immunoglobulin (Ig) has been the unique feature by which the B cell origin of these lymphoblastoid lines has been ascertained. In the present studies, a number of unusual lymphoblastoid lines were obta… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
12
0

Year Published

1981
1981
2014
2014

Publication Types

Select...
5
4

Relationship

2
7

Authors

Journals

citations
Cited by 22 publications
(12 citation statements)
references
References 14 publications
0
12
0
Order By: Relevance
“…There is suggestive evidence that primarily the more mature B cells are induced by pokeweed mitogen. On the contrary, sensitivity to Epstein-Barr viral infection probably develops very early in B cell ontogeny, perhaps even prior to the appearance of surface immunoglubulin [18]. Thus, purified B cells from umbilical cord blood respond vigorously to Epstein-Barr virus, but poorly to pokeweed mitogen, even in the presence of an accessory source of mature T cells [31,40].…”
Section: Inducers Of Rheumatoid Factor In Ldvo and In Vitromentioning
confidence: 87%
“…There is suggestive evidence that primarily the more mature B cells are induced by pokeweed mitogen. On the contrary, sensitivity to Epstein-Barr viral infection probably develops very early in B cell ontogeny, perhaps even prior to the appearance of surface immunoglubulin [18]. Thus, purified B cells from umbilical cord blood respond vigorously to Epstein-Barr virus, but poorly to pokeweed mitogen, even in the presence of an accessory source of mature T cells [31,40].…”
Section: Inducers Of Rheumatoid Factor In Ldvo and In Vitromentioning
confidence: 87%
“…By immunofluorescence, Josh 7 and Reh did not make any Ig whereas Nalm 12 made only cytoplasmic t~ chains. These cell lines represent human precursor and pre-B cell lines (11,12). Immunofluorescence studies as shown in Fig.…”
Section: Methodsmentioning
confidence: 99%
“…Human non-T ALL cell lines Reh and Nalm 12 (11) were kindly provided by Dr. P. Ralph of the Memorial Sloan-Kettering Cancer Center. Cell line Josh-7 was derived from a patient with X-linked agammaglobulinemia (12). It has little detectable Ig and is HLA-DR ÷, CALLA +, and TdT-.…”
Section: Methodsmentioning
confidence: 99%
“…cell-depleted human bone marrow cells as described (9). These cells express: WIH8, y' k`; WIH10, a'x' ; WIH14, a'x' ; WIH20, la'x' ; WIH67, y' X' ; and KAW15, y' X' .…”
mentioning
confidence: 99%